AN EFFECT OF PRODUCT QUALITY ON CUSTOMER SATISFACTION AT KFC FAST FOOD RESTAURANT BRANCH TITI KUNING - Aminuddin Aminuddin (CERED Indonesia Institute, 2021)
Product quality is a product or service that is produced and provides a high-quality value to meet the needs of the community. As the fulfillment of community needs, customer satisfaction is one of the most important things in evaluating a product. The more satisfied customers are with the products used, the better the quality provided. This paper is entitled “The Effect of Product Quality on Customer Satisfaction at Fast Food Restaurants KFC Branch Titi Kuning, Medan